The role of the social report in the development of the social dashboard within the industrial company: Case study of the Batna cement company - BOUHADID, Leila; AICHI, Kamel (Dirassat Journal Economic Issue, 2015)
This study aims to identify the social outcome, and to address the social dashboard, and to highlight the contribution of social outcome in the preparation of the social dashboard in the cement organisation Batna during the period (2011-2013). The study result showed that the social outcome help in the preparation of the social dashboard cement organisation batna through the information provided, which are basic rules to calculate the Ratios and do comparisons always to previous years, and is the most important indicators examined by the social dashboard in: employment, recruitment, configuration, absence and wages.